ANALISIS PENGARUH STRES KERJA DAN GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI PERUSAHAAN DAERAH BANK PERKREDITAN RAKYAT BKK KABUPATEN DEMAK - Rochmanasari, Dina; Mudiantono, Mudiantono (Diponegoro Journal of Management, 2013)
An established company in general has several purposes, such as to obtain the maximum profit in which the banking company can be seen from the side of the rentability. To achieve this requires some resources, particularly human resources. They are the ones who will market the products of the company to achieve the ultimate goal. A number of people organized in one organization or company to achieve certain objectives requires a systematic and structured order set out in the form  of  organizational  structure.  This  is  meant  to  guarantee  a  positive  interaction  with  one another. In addition the work can run in accordance with their job description and not to mention the hierarchy is known who leads and who is led. It is therefore expected that all obstacles in the company like stress of work can be overcome and the leadership functions are able to run, so that the performance of employees will go on well.The purpose of this study is to find out the effect of work stress and leadership style on the employee’s performance of PD. BPR BKK Demak regency. The number of population in the study is as many as 102 people and the number of samples is as many as 78 people. While the analysis tool used is multiple regression.After the data are collected, the process of scoring, validity, reliability test, assumptions test, and then the final stage is the multiple regression test. From the results of hypothesis testing can beconcluded that the work stress variables (X1) has positive effect and it is significant on theemployee’s performance (Y). Similarly to the leadership style variable (X2) has a positive and significant impact on the employee’s performance (Y)